2020
DOI: 10.3389/fonc.2020.00853
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Analysis Reveals the Underlying Association Between CTNNB1 Mutation and Immunotherapy in Hepatocellular Carcinoma

Abstract: Background: Tumor mutational burden (TMB) was verified to be closely associated with immune checkpoint inhibitors, but it is unclear whether gene mutation has an effect on immunotherapy of hepatocellular carcinoma (HCC). This research aimed to investigate the underlying correlation between gene mutation and immunotherapy in HCC. Methods: The somatic gene mutation data and gene expression data were retrieved from International Cancer Genome Consortium database and The Cancer Genome Atlas (TCGA) database. The mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…In combination with the aforementioned findings, we attributed the poor prognosis of KICH patients with a high TMB to the higher frequency of TP53 mutations ( Table S1 A). In patients with LIHC, we found that the CTNNB1 mutation group had a higher TMB ( Table S1 A), which was significantly correlated with a better prognosis in LIHC [65] . The TMB of the TP53 mutation group was also higher ( Table S1 A), which has previously been reported to be related to a higher TMB and worse outcome in patients with hepatocellular carcinoma [66] .…”
Section: Discussionmentioning
confidence: 83%
“…In combination with the aforementioned findings, we attributed the poor prognosis of KICH patients with a high TMB to the higher frequency of TP53 mutations ( Table S1 A). In patients with LIHC, we found that the CTNNB1 mutation group had a higher TMB ( Table S1 A), which was significantly correlated with a better prognosis in LIHC [65] . The TMB of the TP53 mutation group was also higher ( Table S1 A), which has previously been reported to be related to a higher TMB and worse outcome in patients with hepatocellular carcinoma [66] .…”
Section: Discussionmentioning
confidence: 83%
“…The presence of the CTNNB1 mutation has also been associated with a better response to immunotherapy in other cancers. [16,17] This could be explained by the role of CTNNB1 in modulating the activity of NK cells by affecting CD96. Further investigations should be performed to better understand the role of this mutation in non-small cell lung cancer.…”
Section: -Discussionmentioning
confidence: 99%
“…Therefore, it can be considered as a reliable biomarker for HCC response to immunotherapy. 77 Next generation sequencing (NGS) seems to be beneficial in clinical course and for treatment of HCC patients, as it can provide predictions about advantages of immunotherapy in HCC patients. The mutation in CTNNB1 and abnormal activation of Wnt/β-catenin signaling reduce response of HCC patients to immune checkpoint inhibitors.…”
Section: Beta-catenin and Hepatocellular Carcinomamentioning
confidence: 99%